PERENCANAAN DINDING PENAHAN TAMBAHAN PADA SUNGAI KONTO DI KECAMATAN PUJON KABUPATEN MALANG - Soka, Anselmus; Suhudi, Suhudi; Arifianto, Andi Kristafi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Retaining wall has function to hold the soil and prevent it from sliding danger. Because of load rain, heavy soil or because of the load acting. At this time, the construction of retaining wall is very often used in civil works construction although the retaining wall had been famous in the world. The occurrence of avalanches on the Konto river in Jalan Abd.Manan Wijaya Pujon caused by the dimensions of the retaining wall is too small so unstable to the safety factor (fs), the value of the safety factor in the review is a safety factor to bearing capacity, shear forces and stability against roll style. The purpose of this study was to increase the strength of an existing retaining wall so it can prevent sliding because of the location of research there on the corner of the street and there is a bridge crossing the local residents as well as the access to the main line Malang - Kediri. Planning additional soil retaining walls using a modification of gravity type retaining wall masonry and reinforced concrete times. Dimensional stability against sliding wall: 2.33> 1.5 (safe) and was stable against the bolsters: 5.3> 1.5 (safe). Keywords: Bend, Ancillary, Stability Retaining Walls.